2022
DOI: 10.3390/en15228371
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Biofuel Briquettes Obtained from Greenhouse Waste Using a Mobile Prototype Briquetting Machine with PTO Drive

Abstract: Turkey has a large agricultural area and produces 55–60 million tons of biomass waste/year. This study aimed to obtain bio-briquettes from three types of dried greenhouse wastes and to determine their strength parameters. A prototype of a mobile briquetting machine driven by power take-off (PTO), with hydraulic pistons, and comprising a shredder and grinding or crushing unit with a briquetting pressure in the range of 0–190 MPa, was used. The physical parameters of the obtained briquettes were determined, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Kaliyan and Morey reported that the durability value of briquettes obtained from corn cobs ground at 150 MPa compression pressure was between 88.2 and 92.3% 38 . Kabas determined the tumbler index value of briquettes obtained from nutshell fruit wastes between 95% and 97% and the tumbler index value of briquettes obtained from greenhouse wastes as 94–98% in their studies 18,19 …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Kaliyan and Morey reported that the durability value of briquettes obtained from corn cobs ground at 150 MPa compression pressure was between 88.2 and 92.3% 38 . Kabas determined the tumbler index value of briquettes obtained from nutshell fruit wastes between 95% and 97% and the tumbler index value of briquettes obtained from greenhouse wastes as 94–98% in their studies 18,19 …”
Section: Resultsmentioning
confidence: 97%
“…While determining the tumbler index and shatter index of the briquettes, the broken briquette pieces were sieved using a sieve with an opening of 20 mm and the particles remaining on the sieve were not considered as loss 17–19 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomass boasts the capacity to be stored and subsequently utilized as needed. Moreover, the decreases in emissions of greenhouse gases, enhanced safety measures, and the progression of the indigenous economy are indeed a few of the advantages intrinsic to the utilization of biomass [5].…”
Section: Introductionmentioning
confidence: 99%